1984
DOI: 10.1177/019262338401200212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Photo-Induction and Microsomal Activation of Polycyclic Hydrocarbons with Different Oncogenic Potency

Abstract: The binding of five polycyclic aromatic hydrocarbons (PAH) (anthracene (A), benzo(a)anthracene (BA), dibenz(a,h)anthracene (DBA), benzo(a)pyrene (BP) and 7,12-dimethylbenz(a)anthracene (DMBA)) to calf thymus DNA and synthetic polyribonucleotides was studied. Binding was mediated by near-ultraviolet (NUV) irradiation and 3-methylcholanthrene-induced microsomes from rat liver, in order to compare the effectiveness of these two activating systems in forming in vitro intermediates capable of binding covalently to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…An alternative mechanism that might contribute to the increasing trend of DNA adducts in summer is represented by photoactivation of pollutants. The formation of PAH‐photoadducts, i.e., anthracene, benzo(a)anthracene, dibenz(a,h)anthracene, benzo(a)pyrene, 7,12‐dimethylbenz(a)anthracene and 1‐hydroxypyrene DNA adducts, has been shown to be induced in vitro by ultraviolet irradiation 33, 34. Phototransformation of 2‐aminofluorene into proximate mutagens/carcinogens has been shown35 after exposure of solutions to near ultraviolet light (wavelengths of 320–400 nm), and aflatoxin‐N7 guanine photoadduct formation has also been reported 36…”
Section: Discussionmentioning
confidence: 99%
“…An alternative mechanism that might contribute to the increasing trend of DNA adducts in summer is represented by photoactivation of pollutants. The formation of PAH‐photoadducts, i.e., anthracene, benzo(a)anthracene, dibenz(a,h)anthracene, benzo(a)pyrene, 7,12‐dimethylbenz(a)anthracene and 1‐hydroxypyrene DNA adducts, has been shown to be induced in vitro by ultraviolet irradiation 33, 34. Phototransformation of 2‐aminofluorene into proximate mutagens/carcinogens has been shown35 after exposure of solutions to near ultraviolet light (wavelengths of 320–400 nm), and aflatoxin‐N7 guanine photoadduct formation has also been reported 36…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work demonstrated that anthracene underwent binding with DNA (Ts'o and Lu, 1964;Craig and Isenberg, 1970;Prodi et al, 1984) and that covalent bond formation occurred upon irradiation with DNA (Blackburn et al, 1973; Sinha R. W. TUVESON er a/. able of operating either as a Type I or Type I1 sensitizer.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that none of the defects in the major repair systems sensitize the cells to inactivation by anthracene plus NUV might be interpreted to mean that damage to DNA (if any) is not particularly lethal in this treatment. However, we cannot exclude the possibility that DNA lesions produced by anthracene plus NUV might actually be repaired by one of the mismatch repair systems (Radman and Wagner, 1986). We are currently developing strains to check on this possibility.…”
Section: Inactivation Of E Coli Strains By Anthracene Plus Nuvmentioning
confidence: 99%
“…For certain PAHs, the increase in toxicity can be six-to sevenfold (Swartz et al, 1997).In vivo, the formation of covalent PAH-DNA adducts through irradiation with light may compete with enzymatic activation. Indeed, irradiation of benzo [a]pyrene or DMBA inside the cells tends to lower the amount of covalent DNA adducts formed by enzymatic activation (Prodi et al, 1984), an effect that was mainly attributed to photodegradation of the PAHs. Photo-oxidation of the unsubstituted PAHs -two-ring naphthalene (Vialaton et al, 1999); three-ring anthracene (Mallakin et al, 2000) and phenanthrene (Wen et al, 2002); four-ring benz [a]anthracene (Dong et al, 2002) and pyrene (Sigman et al, 1998); and five-ring benzo [a]pyrene (Lee-Ruff et al, 1988) -can produce respective quinones, ring-open products or hydroxy-substituted products.…”
Section: Phototoxicitymentioning
confidence: 99%